2006
DOI: 10.1515/znb-2006-0808
|View full text |Cite
|
Sign up to set email alerts
|

The Structure And Tautomerism Of Cyameluric Acid*

Abstract: The single crystal X-ray structure of the DMSO solvate of cyameluric acid C 6 N 7 O 3 H 3 · 3DMSO, 2b' has been determined. The results show that the most stable tautomer of solid cyameluric acid is the tri-keto form 2b with C 3h symmetry. 1 H and 13 C NMR data indicate that this isomer is also present in solution, with slow interchange of the N-H protons. This confirms previous theoretical results although almost all derivatives reported in the literature are derivatives of the tri-hydroxy tautomer 2a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Therefore, it can be predicted that the most stable form of free cyameluric acid C 6 N 7 O 3 H 3 has the same structure with C 3h symmetry. This conclusion is strongly supwww.chemeurj.org ported by very recent structural examinations of a DMSO solvate [52] and a trihydrate [53] of cyameluric acid. The thermal stability of 5 and 6 is decreased compared with alkali cyamelurates M 3 Compound 4 can be considered as a tris-trimetylsilyl ester of 1-4-7, containing fourfold coordinated silicon atoms.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, it can be predicted that the most stable form of free cyameluric acid C 6 N 7 O 3 H 3 has the same structure with C 3h symmetry. This conclusion is strongly supwww.chemeurj.org ported by very recent structural examinations of a DMSO solvate [52] and a trihydrate [53] of cyameluric acid. The thermal stability of 5 and 6 is decreased compared with alkali cyamelurates M 3 Compound 4 can be considered as a tris-trimetylsilyl ester of 1-4-7, containing fourfold coordinated silicon atoms.…”
Section: Resultsmentioning
confidence: 86%
“…For a review of tri-s-triazines, see: Schwarzer et al (2013). For crystal structures and a comprehensive analysis of cyameluric acid, see: Sattler & Schnick (2006); Wagler et al (2006); Seyfarth et al (2008). For the synthesis of unsymmetrically substituted tri-s-triazines, see: Schwarzer & Kroke (2010, 2011.…”
Section: Related Literaturementioning
confidence: 99%
“…Cyameluric acid and its salts were characterized by FTIR spectroscopy by Finkel'shtein and Spridonova . In contrast to cyanuric acid C 3 N 3 O 3 H 3 , which was found to exist in the keto‐form, the tautomeric form of cyamluric acid could not be distinguished clearly for a long time and many publications dealt with this question . Different crystal structures finally showed that the keto form is favored in the solid state .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cyanuric acid C 3 N 3 O 3 H 3 , which was found to exist in the keto‐form, the tautomeric form of cyamluric acid could not be distinguished clearly for a long time and many publications dealt with this question . Different crystal structures finally showed that the keto form is favored in the solid state . Besides, the crystal structures of cyameluric acid, crystal structures of some alkali metal cyamelurates were reported .…”
Section: Introductionmentioning
confidence: 99%